Pengaruh ROA, TATO, CR, Dan DER Terhadap Nilai Perusahaan Sebelum Dan Sesudah Merger & Akuisisi Di BEI 2015-2020 - Hadi, Yulianto -; Hendriani, Maria; Jamaludin, Ali; Soraya, Fovi (Fakultas Ekonomi dan Bisnis Universitas Islam DR KH EZ Mutaqien, 2024)
Abstract The purpose of this research is to analyze Return On Assets (ROA), Total Asset Turnover (TATO), Current Ratio (CR), and Debt to Equity Ratio (DER), on company value. This research uses a saturated sample of 12 companies 3 years before and 3 years after mergers & acquisitions in companies listed on the Indonesia Stock Exchange (BEI) 2015-2020. The analytical method used is multiple linear regression analysis with eview 10. The results of this research show 3 years before Mergers & Acquisitions. that ROA has a significant positive effect on company value, TATO, (CR), and (DER) have no effect on company value and simultaneously have no effect on company value and 3 Years After Mergers & Acquisitions that ROA, TATO, CR have a significant positive effect on The value of the company. and (DER) has no effect on company value. simultaneously has a significant positive effect on company value Keywords: Return On Asset, Total Asset Turnover, Current Ratio dan Company Value